Marketing research in terms of the prospects for creating a gel based on the phyto-substance Parmelia sulcata - Blahovisna, Kateryna; Zuikina, Svitlana (Annals of Mechnikov's Institute, 2025)
The aim of the study. To conduct marketing and analytical research of the pharmaceutical market of Ukraine to determine the assortment of domestic and imported drugs with burn-healing and wound-healing effects, as well as to evaluate the prospects for creating a new gel based on Parmelia sulcata liquid extract. Materials and Methods. Information-analytical, bibliosemantic, and marketing research methods were used. The data sources included the State Register of Medicinal Products of Ukraine, the Compendium reference book, and publications of domestic and foreign scientists. A comparative analysis of the range of medicinal products by dosage forms, active pharmaceutical ingredients, origin, and manufacturers was performed. Results. It was found that most burn-healing drugs are presented in soft dosage forms, particularly ointments (60.4%) and creams (26.4%), while gels account for only 5.6%. Medicines containing synthetic components prevail (over 70%), which leads to the risk of microbial resistance and allergic reactions. The share of herbal-based preparations does not exceed 25%. Parmelia sulcata raw material contains usnic acid, flavonoids, polysaccharides, and amino acids, which provide antimicrobial, anti-inflammatory, and reparative effects. The obtained results confirm the feasibility of developing a domestic hydrophilic gel containing Parmelia sulcata liquid extract as a promising agent for the treatment of burn injuries. Conclusions. It has been shown that the use of phytosubstances is an effective approach to improving the quality and safety of topical medicinal products. The creation of a gel based on Parmelia sulcata liquid extract has significant potential for the pharmacotherapy of burns and wounds under both military and civilian conditions.